Third Worlds, Coolie and Coolitude: Unravelling the long arm of history - Pio, Edwina; Moon, Paul (Te Kaharoa, 2021)
Sugar dictated the fortunes of many countries in the British Empire in the nineteenth century. With the abolition of slavery, thousands of indentured labour or coolies from the Indian subcontinent, filled the labour gap. The word coolie was derogatory, referring to a marginalized underclass, whereas the word coolitude evokes and acknowledges agency. Our article revolves around the question: How does a historical lens evoke understandings of ethnic minorities (EM) at work in contemporary organisations? We illuminate a historical lens (the eternal present and linear progression, historical determinism and structuralism, and evoking the past), to provoke reflections on how on-going marginalisation of ethnic minorities at work, may be tethered to a coolie template. We weave conceptual understandings of history, indentured labour and EM in an interdisciplinary manner to evoke reflection by policy framers and managers on how the long arm of history may be implicated and unravelled. We suggest that such insights are necessary to highlight perceptions of coolitude as an alternative epistemology pertaining to EM at work